ARTIKEL Dampak kepuasan kerja terhadap kinerja karyawan SDN Warungdowo 1 - RAMDHANI, REVIANDY AZHAR; ROJABI, MUHAMMAD NAFIS; MUBAROK, MOCH CHUSNI; KHOLIS, NUR (Universitas Multi Data Palembang, 2024)
Abstract: This qualitative study explores the relationship between job satisfaction and employee performance in public elementary school (SDN) Warungdowo 1. By interviewing 15 employees from a variety of positions, including teachers, administrative staff, and janitors, we analyzed the factors that influenced their perceptions of job satisfaction and performance. The results showed that there is a positive correlation between job satisfaction and employee performance. Factors that affect job satisfaction include the work environment, support from leadership, recognition of contributions, and career development opportunities. Respondents who feel satisfied with their work tend to show better performance, such as high commitment to tasks, initiative in solving problems, and active participation in achieving school goals. This study provides a deep understanding of the importance of job satisfaction management in improving employee performance in educational institutions. Practical implications include the need for organizational policies that support employee well-being and strategies to improve job satisfaction in the educational work environment. This study contributes to the human resource management literature by revealing an important relationship between job satisfaction and employee performance at SDN Warungdowo 1. Keywords— Job satisfaction, employee performance, education, human resource management, work environment.